THE EFFECT OF WATERING ON WATER MANAGEMENT BY HYDROGELS ON THE GROWTH OF Shallot Plants - Sulaiman Ginting (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
Onion red is Wrong One commodity vegetables flagship that has been for a long time attempted by farmer in a way intensive . Commodity vegetables This including to in group spice No working substitution _ as spice flavoring food as well as material drug traditional . Onion red Also is Wrong One commodity vegetables that have mark economical high , fine reviewed from side fulfillment consumption national , source income farmers , as well as its potential as producer foreign exchange country. Efforts to cultivate shallots have recently often failed due to climate change in the form of El-Nino or La-Nina. The occurrence of drought due to a long dry season causes watering costs to increase, whereas when there is high rainfall the water supply becomes excessive so that planting locations become flooded, which results in suboptimal plant growth. To overcome this, a technology package is needed that is able to manage water so that plant growth remains normal. Hydrogel is network macromolecules that can absorb And release the hanging water on stimulation external , such as pH, humidity , temperature , and pressure environment surroundings . Application hydrogel in the field agriculture has proven capable increase efficiency water usage , which is also capable decrease erosion. Objective from study This For know influence sprinkling to water management by hydrogel on growth plant onion red . Study This use Design Random Complete (RAL) Non Factorial with watering interval treatment consisting of of 4 levels namely A 0 (2 x 1 day), A 1 (1 x 3 days), A 2 (1 x 2 days) and A 3 (1 x 1 day). Observed parameters is tall plants , quantity leaves , quantity sapling And heavy tubers . Data analyzed with analysis of variance (ANOVA) and if there is influence real so done test carry on use test distance double Duncan on level significance 5%. The results showed that the watering interval treatment have a real effect on is tall plants , quantity leaves , quantity sapling And heavy tubers . Application hydrogel can save sprinkling from One One day become once a day , however No effective in overcome puddle consequence excessive water supply.